Method for manufacturing bond magnet and bond magnet

Through compression molding and thermosetting resin curing technology, a combination magnet with high filling rate and good shape processing ability is produced, solving the problems of difficult magnet shape processing and insufficient magnetic properties in the prior art.

JP2025040848APending Publication Date: 2025-03-25ZEON CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023147909
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The prior art is difficult to manufacture a combined magnet with high fill rate and good shape processing capability without decreasing magnetic properties.

Method used

Combined magnets are manufactured using compression molding, including compressed magnetic powder forming molds, grounding steps connect multiple molds together, apply low viscosity thermosetting resin, and cure under heating to form bonded magnets.

Benefits of technology

The bonding magnet with high filling rate magnetic powder is realized, and the processing capability of any shape is achieved, while avoiding the reduction of magnetic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025040848000001_ABST
    Figure 2025040848000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing a bond magnet which is filled with magnet powders densely and is in an arbitrary shape, and the bond magnet.SOLUTION: A method for manufacturing a bond magnet 100 includes: a formation step of compressing particles 10 of magnetic powders and obtaining formation bodies 1 and 2; grounding at least two formation bodies and holding the formation bodies to obtain a connector body; and immersing a thermosetting composition in the connector body. A thermosetting resin 3 has a viscosity of 200 mPa s at a maximum.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for manufacturing a bonded magnet and to a bonded magnet. [Background technology]

[0002] There are various types of magnets, including cast magnets, which have been used for a long time, sintered magnets made by sintering magnetic powder, and bonded magnets, which are made by molding magnetic powder with a resin binder. Of these, bonded magnets have inferior magnetic properties to cast magnets and sintered magnets, but because they contain resin, they are easy to deform and process, and can be easily processed into any shape, meaning they have good shape processability. However, because bonded magnets contain resin, it is difficult to increase their strength sufficiently, and there are also problems with the fact that the magnetic properties become weaker than other magnets as the amount of magnetic powder per unit volume decreases.

[0003] Patent Document 1 discloses a method for manufacturing a bonded magnet and the bonded magnet. This method for manufacturing a bonded magnet includes a first compression step in which a magnetic powder with an average particle size of 10 μm or less is compressed while being magnetically oriented to obtain a first compact, a second compression step in which the first compact is brought into contact with a thermosetting resin with a viscosity of 200 mPa·S or less and then compressed to obtain a second compact, and a heat treatment step in which the second compact is heat treated. It is said that the bonded magnet manufactured by this method for manufacturing a bonded magnet has improved magnetic properties due to the high filling rate and orientation rate of the magnetic powder. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-109840 A Summary of the Invention [Problem to be solved by the invention]

[0005] For example, motors for electric vehicles (EVs) require precise magnetic control. For example, precise magnetic control can be achieved by devising the shape of the magnet inside the motor. In such cases, it may be necessary to mold the magnet into a complex shape to achieve precise magnetic control. However, it is not easy to mold a sintered magnet into a complex shape.

[0006] In contrast, if a bonded magnet has good shape processability, it is believed that complex shapes can be realized for precise magnetic control. However, as mentioned above, the problem with bonded magnets is that their magnetic properties are inferior to those of cast magnets and sintered magnets. In contrast, the manufacturing method for bonded magnets and bonded magnets disclosed in Patent Document 1 are said to have a high filling rate and good magnetic properties, but do not fully utilize the bonded magnet's characteristic of good shape processability. In other words, the manufacturing method for bonded magnets and bonded magnets disclosed in Patent Document 1 are not easy to form into any shape.

[0007] The present disclosure has been made in consideration of the above-mentioned circumstances, and its purpose is to provide a bonded magnet manufacturing method and a bonded magnet that have a high filling rate of magnetic powder and can produce a bonded magnet of any shape. [Means for solving the problem]

[0008] In order to achieve the above object, the manufacturing method of a bonded magnet and the bonded magnet according to the present disclosure are as follows.

[0009] [1] The method for producing a bonded magnet according to the present disclosure comprises: a molding step of compressing and molding the magnetic powder to obtain a green body; a grounding step in which two or more of the molded bodies are grounded and held together to form a connected body; and an impregnation step of impregnating the connector with a thermosetting composition, The thermosetting resin has a viscosity of 200 mPa·s or less.

[0010] According to the above manufacturing method, it is possible to realize a bonded magnet having a high filling rate of magnetic powder and having any desired shape.

[0011] [2] The method for producing the bonded magnet described in [1] above comprises the steps of: The surface roughness of the contact surface of each of the molded bodies in the connecting body may be 50 μm or less.

[0012] According to the above manufacturing method, it may be possible to avoid a decrease in the mechanical strength of the bonded magnet.

[0013] [3] The method for producing the bonded magnet described in [1] or [2] above comprises the steps of: The method further includes a curing step of curing the thermosetting composition impregnated in the connector, In the curing step, forming a resin layer between one of the molded bodies and the other of the molded bodies by hardening the thermosetting composition; The resin layer may have a thickness of 2 μm or more and 50 μm or less.

[0014] According to the above manufacturing method, it may be possible to avoid a decrease in the strength of the bonded magnet.

[0015] [4] The method for producing a bonded magnet according to any one of [1] to [3] above, In the molding step, the mixed powder of the magnetic powder and the surface treatment agent is compression molded to form the molded body, The surface treatment agent may be mixed in an amount of 5 parts by mass or less with respect to 100 parts by mass of the magnetic powder.

[0016] According to the above-mentioned manufacturing method, the strength of the compact or bonded magnet is increased, and the handleability of the compact may be improved.

[0017] [5] The bonded magnet according to the present disclosure comprises a first compact and a second compact in which magnetic powder is fixed with a thermosetting resin; A resin layer disposed between the first molded body and the second molded body, the resin layer is formed of the thermosetting resin, The maximum thickness of the resin layer is 2 μm or more and 50 μm or less.

[0018] The bonded magnet has a high magnetic powder filling rate and can be formed into any desired shape. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 is a cross-sectional view showing a schematic configuration of a bonded magnet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] A method for producing a bonded magnet and a bonded magnet according to an embodiment of the present disclosure will be described with reference to the drawings. First, an overview of the method for producing a bonded magnet and the bonded magnet according to an embodiment of the present disclosure will be described.

[0021] The method for producing the bonded magnet according to this embodiment includes a molding step of compressing and molding a magnetic powder to obtain a molded body, a grounding step of grounding and holding two or more of the molded bodies together to form a connected body, and an impregnation step of impregnating the connected body with a thermosetting composition having a viscosity of 200 mPa s or less.

[0022] According to the manufacturing method of the bonded magnet according to this embodiment, it is possible to realize a bonded magnet with a high filling rate of magnetic powder and in any shape.

[0023] 1, the bonded magnet 100 according to this embodiment comprises a first compact 1 and a second compact 2 in which magnetic powder particles 10 are fixed with a thermosetting resin 3, and a resin layer 4 disposed between the first compact 1 and the second compact 2. The resin layer 4 is formed from the thermosetting resin 3. The maximum thickness of the resin layer 4 is 2 μm or more and 50 μm or less.

[0024] Bonded magnet 100 can be manufactured by the manufacturing method for a bonded magnet according to this embodiment. Bonded magnet 100 has a high filling rate of magnetic powder and can be formed into any shape.

[0025] A method for producing a bonded magnet according to an embodiment of the present disclosure will be described in detail below.

[0026] As described above, the method for producing a bonded magnet according to this embodiment may include a molding step for obtaining a molded body, a grounding step for connecting two or more molded bodies to form a connected body, an impregnation step for impregnating the connected body with a thermosetting composition, and a curing step for curing the thermosetting composition impregnated in the connected body. The bonded magnet produced by the method for producing a bonded magnet according to this embodiment may be further magnetized as necessary.

[0027] The molding process is a process in which the magnetic powder is compressed and molded to obtain a molded body as a precursor of the bonded magnet. This molded body is a so-called green compact. The magnetic powder may be mixed with a surface treatment agent. That is, in the molding process, a mixed powder in which a predetermined amount of a surface treatment agent is added to the magnetic powder may be compression molded to obtain the molded body.

[0028] The compression molding in the molding step may be performed using a metal mold. The metal mold may have, for example, a first metal mold having a recess (cavity) into which the magnetic powder is charged, and a second metal mold having a protrusion (core) that fits into the recess of the first metal mold. The compression molding may be performed, for example, by charging a predetermined amount of magnetic powder into the recess of the first metal mold, and applying pressure to the metal mold so as to compress the first metal mold and the second metal mold in the direction in which they approach each other, with the protrusion of the second metal mold fitted into the recess of the first metal mold.

[0029] In compression molding, the pressure applied to the mold during compression (hereinafter sometimes referred to as molding pressure) is not particularly limited. In order to produce a magnet with a higher filling rate, the molding pressure should be 1 t / cm 2 More than 11t / cm 2 Less than 2t / cm is preferable. 2 More than 5t / cm 2 More preferably, the molding pressure is 1t / cm 2 If the molding pressure is 11 t / cm or more, the filling rate in the molded body is sufficiently high. 2 If it exceeds this value, the density of the molded body will be too high, which may result in poor resin impregnation, as described below, and thus a decrease in the strength of the resulting bonded magnet.

[0030] Compression in compression molding may be performed two or more times. For example, the mold may be compressed at a first pressure as a preliminary compression, and then a second pressure higher than the first pressure may be used for finishing compression to form a molded body.

[0031] The compression molding may be performed while magnetically orienting the magnetic powder. When magnetic orientation is performed during compression molding, the magnitude of the external magnetic field applied for magnetic orientation is not particularly limited, but is preferably 0.5 T or more, and more preferably 1 T or more. If it is less than 0.5 T, the magnet tends not to be sufficiently oriented. The upper limit is preferably 10 T or less. If it exceeds 10 T, the magnetic powder will be excessively magnetized, making it impossible to perform sufficient molding.

[0032] In the molding step, two or more molded bodies are molded. Each molded body is molded separately. Each molded body may be manufactured in the same mold, or may be molded in a different mold. Each molded body may have the same shape, or may have a different shape.

[0033] In the molding process, it is preferable to form a small molded body because the force applied to the mold can be reduced. The molded body may be, for example, a small piece having dimensions of 20 mm or less in three directions (length, width, and height). The shape of the molded body may be a flat plate such as a disk, a cylinder, or a rectangle, or a rectangular parallelepiped.

[0034] The magnetic powder is not particularly limited. An example of the magnetic powder that can be used in the method for producing a bonded magnet according to the present embodiment is a rare earth magnetic material such as SmFeN, NdFeB, or SmCo.

[0035] The SmFeN magnetic powder can be produced by the method disclosed in JP-A-11-189811, the NdFeB magnetic powder can be produced by the HDDR method disclosed in WO-A-2003 / 85147, and the SmCo magnetic powder can be produced by the method disclosed in JP-A-08-260083.

[0036] The particle shape of the magnetic powder is preferably close to spherical. For example, the aspect ratio of the shape of the magnetic powder is preferably 3 or less. When the particle shape of the magnetic powder is, for example, spherical with an aspect ratio of 3 or less, it is easy to realize a bonded magnet with a high filling rate of the magnetic powder.

[0037] In this embodiment, the aspect ratio of the magnetic powder can be determined by observing the magnetic powder with a SEM (scanning electron microscope), measuring the maximum diameter (long diameter) and the particle diameter (short diameter) in the direction perpendicular to the maximum diameter for any 50 particles, and calculating the average value of the ratio of the long diameter to the short diameter (long diameter / short diameter). The magnification ratio during SEM observation may be appropriately changed depending on the particle diameter. The magnification ratio may be, for example, 100 to 1000 times.

[0038] The particle size of the magnetic powder may be, for example, 3 μm or more and 300 μm or less in terms of the median diameter (50% particle size, so-called D50). In this embodiment, the particle size and particle size distribution of the magnetic powder can be determined as volume-based values ​​measured using a laser diffraction / scattering type particle size distribution measuring device (manufactured by Horiba, Ltd., model "LA960"). For measurement using the laser diffraction / scattering type particle size distribution measuring device, a suspension in which 1 g of the magnetic powder to be measured is dispersed in methyl ethyl ketone as a solvent may be used.

[0039] The magnetic powder may be treated with phosphoric acid, which forms a passivation film having P-O bonds on the surface of the magnetic powder.

[0040] The phosphating is carried out by reacting the magnetic powder with a phosphating agent, which may include, for example, phosphates such as orthophosphoric acid, sodium dihydrogen phosphate, potassium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, zinc phosphate, calcium phosphate, etc., inorganic phosphoric acids such as hypophosphorous acid, hypophosphites, pyrophosphoric acid, polyphosphoric acid, etc., organic phosphoric acids, and salts thereof.

[0041] The surface treatment agent may be an additive that protects the surface or modifies the surface properties, such as preventing oxidation of the magnetic powder, compact, or bonded magnet, or improving wettability in the impregnation process of the linking body, or an additive that functions as a so-called binder, improving the binding force between the particle surfaces of the magnetic powder in the compact. Examples of the surface treatment agent include alkyl silicates that perform silica treatment on the particle surfaces of the magnetic powder, silane coupling agents that perform silane treatment, and surfactants such as nonionic surfactants. The surface treatment agent is not limited to one type, and two or more types may be used in combination.

[0042] The surface treatment agent is preferably mixed in an amount of 5 parts by mass or less, and more preferably 1 to 3 parts by mass, per 100 parts by mass of the magnetic powder. This may increase the strength of the molded body or bonded magnet. It may also improve the handleability of the molded body.

[0043] The magnetic powder is preferably surface-treated with a coupling agent, preferably silane-treated, in order to improve the magnetic properties of the magnetic powder, improve wettability with the thermosetting composition in the impregnation step described below, and increase the mechanical strength of the bonded magnet. Note that the coupling agent has two or more different groups in its molecule, one of which has a group that reacts with inorganic materials and the other has a group that reacts with organic materials.

[0044] The coupling agent is not particularly limited, and examples of the coupling agent include a silane coupling agent having no alkyl or alkenyl group with a carbon number of 8 to 24, and a coupling agent having an alkyl or alkenyl group with a carbon number of 8 to 24.

[0045] Examples of coupling agents having an alkyl or alkenyl group having 8 to 24 carbon atoms include silane coupling agents, phosphate coupling agents, and hydrogen phosphite coupling agents. These coupling agents may be used alone or in combination of two or more.

[0046] Examples of silane coupling agents having an alkyl group or an alkenyl group having 8 to 24 carbon atoms include those represented by the following general formula: Specific examples include decyltrimethoxysilane, decyltriethoxysilane, dodecyltrimethoxysilane, dodecyltriethoxysilane, hexadecyltrimethoxysilane, hexadecyltriethoxysilane, octadecyltrimethoxysilane, octadecyltriethoxysilane, octyltriethoxysilane, and the like, with octadecyltriethoxysilane and octyltriethoxysilane being particularly preferred. (R 1 ) x Si(OR 2 ) (4-x) (R 1 is C n H 2n+1 or C n H 2n-1 where n is an integer of 8 to 24; R 2 is C m H 2m+1 where m is an integer of 1 to 4, and x is an integer of 1 to 3. In addition, the group in the silane coupling agent that reacts with the organic material refers to, for example, a group in which a silicon atom is directly bonded to a carbon atom, and in the above formula, R 1 and the group that interacts with inorganic materials is OR 2 It is.

[0047] Examples of phosphate coupling agents having an alkyl or alkenyl group having 8 to 24 carbon atoms include those represented by the following general formula: Specific examples include didecyl acid phosphate, isodecyl acid phosphate, isotridecyl acid phosphate, lauryl acid phosphate, oleyl acid phosphate, stearyl acid phosphate, isostearyl acid phosphate, tetracosyl acid phosphate, etc., with oleyl acid phosphate being preferred among them. (R 1 O) x PO(OH) (3-x) (R 1 is C n H 2n+1 or C n H 2n-1 where n is an integer of 8 to 24, and x is an integer of 1 or 2. In addition, the group in the phosphate coupling agent that reacts with the organic material is R 1 O, and the group that interacts with inorganic materials is OH.

[0048] The silane coupling agent, phosphate coupling agent or hydrogen phosphite coupling agent having an alkyl group or alkenyl group having 8 to 24 carbon atoms may be used alone or in combination of two or more kinds.

[0049] The treatment with a coupling agent having an alkyl or alkenyl group having 8 to 24 carbon atoms can be carried out by mixing the above-mentioned coupling agent with the magnetic powder and heating it in air to form a coating of the coupling agent. Examples of moisture required for hydrolyzing the coupling agent include acidic aqueous solutions such as an aqueous acetic acid solution, an aqueous sulfuric acid solution, and an aqueous phosphoric acid solution, and basic aqueous solutions such as an aqueous ammonia solution, an aqueous sodium hydroxide solution, and an aqueous potassium hydroxide solution.

[0050] The amount of coupling agent having an alkyl or alkenyl group with a carbon number of 8 to 24 is preferably 0.01 to 1 part by mass, and more preferably 0.05 to 0.5 parts by mass, per 100 parts by mass of the magnetic powder. If the amount is less than 0.01 part by mass, sufficient lubricity cannot be imparted to the magnetic powder, and if the amount is more than 1 part by mass, the mechanical strength of the resulting molded product is impaired.

[0051] Examples of silane coupling agents having no alkyl or alkenyl group and having a carbon number of 8 to 24 include γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane hydrochloride, γ-glycidoxypropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, vinyltriacetoxysilane, γ-chloropropyltrimethoxysilane, hexamethylenedisilazane, γ-anilinopropyltrimethoxysilane, vinyltrimethoxysilane, dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, γ-chloropropylmethyldimethoxysilane, γ-mercaptopropyl Methyldimethoxysilane, methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, vinyltrichlorosilane, vinyltris(β-methoxyethoxy)silane, vinyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, Examples of such silanes include γ-aminopropyltriethoxysilane, ureidopropyltriethoxysilane, γ-isocyanatepropyltriethoxysilane, bis(3-triethoxysilylpropyl)tetrasulfane, γ-isocyanatepropyltrimethoxysilane, vinylmethyldimethoxysilane, 1,3,5-N-tris(3-trimethoxysilylpropyl)isocyanurate, and N-(1,3-dimethylbutylidene)-3-(triethoxysilyl)-1-propaneamine.Examples of silane coupling agents having a cyclic structure include coupling agents having an alicyclic structure such as a monocyclo ring or a bicyclo ring, or an aromatic ring as the cyclic structure. For example, coupling agents having a norbornene skeleton, which is a bicyclo ring, include 2-(bicyclo[2.2.1]hept-5-en-2-yl)ethyltrimethoxysilane, 2-(bicyclo[2.2.1]hept-5-en-2-yl)ethyltriethoxysilane, 2-(bicyclo[2.2.1]hept-5-en-2-yl)trimethoxysilane, 2-(bicyclo[2.2.1]hept-5-en-2-yl)triethoxysilane, 2-(bicyclo[2.2.1]hept-5-en-2-yl)triethoxysilane, [2.2.1]hept-2-enyl)ethynyltrimethoxysilane, 2-(bicyclo[2.2.1]hept-2-enyl)ethynyltriethoxysilane, 2-(bicyclo[2.2.1]hept-5-en-2-yl)hexyltrimethoxysilane, 2-(bicyclo[2.2.1]hept-5-en-2-yl)hexyltriethoxysilane, and coupling agents having an aromatic ring skeleton include N-phenyl-3-aminopropyltrimethoxysilane, N-aminoethylaminomethylphenyl-3-ethyltrimethoxysilane, p-styryltrimethoxysilane, and m-allylphenylpropyltriethoxysilane. These silane coupling agents may be used alone or in combination of two or more. Among these, in terms of wettability and compatibility with the thermosetting composition, slipperiness of the magnetic powder particle surface, heat resistance, and the like, silane coupling agents having a cyclic structure are preferred, silane coupling agents having a norbornene skeleton are more preferred, and 2-(bicyclo[2.2.1]hept-5-en-2-yl)ethyltrimethoxysilane and 2-(bicyclo[2.2.1]hept-5-en-2-yl)ethyltriethoxysilane are even more preferred.

[0052] The treatment with a silane coupling agent having no alkyl or alkenyl group with a carbon number of 8 to 24 can be carried out by mixing the above-mentioned coupling agent with the magnetic powder and heating it in air to form a coating of the silane coupling agent. Examples of moisture required for hydrolyzing the coupling agent include acidic aqueous solutions such as an aqueous solution of acetic acid, sulfuric acid, or phosphoric acid, or basic aqueous solutions such as aqueous ammonia, sodium hydroxide, or potassium hydroxide.

[0053] The amount of the silane coupling agent having no alkyl or alkenyl group and having a carbon number of 8 to 24 is preferably 0.1 to 2 parts by mass, more preferably 0.2 to 1.2 parts by mass, per 100 parts by mass of the magnetic powder. If the amount is less than 0.1 part by mass, the effect of the coupling agent is small, and if the amount exceeds 2 parts by mass, the magnetic powder tends to aggregate and the magnetic properties tend to deteriorate.

[0054] The magnetic powder may be silica-treated with an alkyl silicate in order to protect the magnetic powder from oxidation during the compact manufacturing process and during use of the compact. For example, the magnetic powder may be silica-treated prior to the treatment with the coupling agent. The alkyl silicate is represented by the following general formula, and methyl silicate or ethyl silicate is preferred. SinO (n-1) (OR) (2n+2) (R is an alkyl group, and n is an integer of 1 to 10.)

[0055] The silica treatment can be carried out by mixing the above-mentioned alkyl silicate with the magnetic powder and heating it in air to form a silica coating. Examples of the moisture required for hydrolyzing the silicate include acidic aqueous solutions such as an aqueous solution of acetic acid, sulfuric acid, and phosphoric acid, and basic aqueous solutions such as aqueous ammonia, aqueous sodium hydroxide, and aqueous potassium hydroxide. The amount of the alkyl silicate mixed is preferably 1 part by mass or more and 4 parts by mass or less, more preferably 1.5 parts by mass or more and 2.5 parts by mass or less, relative to 100 parts by mass of the magnetic powder.

[0056] It is preferable that a surfactant such as a nonionic surfactant is added to the magnetic powder in order to improve wettability with the thermosetting composition in the impregnation step described below.

[0057] Examples of nonionic surfactants include polyoxyethylene alkyl ethers such as laureth-4, laureth-7, laureth-9, laureth-21, laureth-23, ceteth-10, ceteth-20, steareth-2, steareth-20, steareth-21, steareth-25, beheneth-20, beheneth-30, oleth-2, and oleth-10. Other examples include polyoxyethylene fatty acid esters such as PEG-25 stearate, PEG-40 stearate, PEG-45 stearate, PEG-55 stearate, PEG-75 stearate, PEG-100 stearate, PEG-150 stearate, and PEG-150 distearate. Other examples include glycerin fatty acid esters such as glyceryl myristate, glyceryl stearate, glyceryl isostearate, glyceryl oleate, glyceryl dioleate, and glyceryl distearate. Other examples include polyglycerin fatty acid esters such as polyglyceryl-10 stearate, polyglyceryl-10 distearate, polyglyceryl-10 tristearate, polyglyceryl-10 pentastearate, polyglyceryl-10 oleate, polyglyceryl-10 isostearate, polyglyceryl-10 myristate, polyglyceryl-10 laurate, polyglyceryl-4 stearate, polyglyceryl-6 stearate, and polyglyceryl-2 stearate. Other examples include polyoxyethylene glycerin fatty acid esters such as PEG-6 glyceryl isostearate, PEG-20 glyceryl triisostearate, PEG-20 glyceryl tristearate, and PEG-7 glyceryl coconut oil fatty acid. Further examples include sorbitan fatty acid esters such as sorbitan laurate, sorbitan palmitate, sorbitan stearate, sorbitan isostearate, sorbitan oleate, sorbitan sesquistearate, sorbitan sesquiisostearate, sorbitan sesquioleate, sorbitan trioleate, sorbitan tristearate, sorbitan olivoyl fatty acid, and sorbitan coconut fatty acid.Further examples include polyoxyethylene sorbitan fatty acid esters such as POE(20) sorbitan laurate, POE(20) sorbitan stearate, POE(20) sorbitan oleate, and POE(20) sorbitan isostearate.

[0058] The grounding step is a step of constructing a connection body in a state where two or more molded bodies are grounded to each other. In the grounding step, adjacent molded bodies are grounded to each other and held so as to maintain a state where their positions are fixed relative to each other.

[0059] In this embodiment, an assembly of two or more molded bodies in which the positions of adjacent molded bodies are fixed with respect to each other in a state where the adjacent molded bodies are grounded is referred to as a connected body. Hereinafter, fixing the positions of two or more adjacent molded bodies with respect to each other in a state where they are placed will be referred to as maintaining the connected body, etc.

[0060] The method for maintaining the connected body is not particularly limited. For example, adjacent molded bodies may be fixed to each other with a jig, or two or more molded bodies may be fitted and fixed in a container such as a mold.

[0061] The contact surface where the molded bodies come into contact with each other preferably has a small surface roughness. Specifically, the surface roughness of the contact surface is 50 μm or less, preferably 40 μm or less, and more preferably 30 μm or less. If the surface roughness of the contact surface is 50 μm or less, it may be possible to avoid a decrease in the mechanical strength of the bonded magnet.

[0062] In this embodiment, the surface roughness of the ground contact surface may be a value measured using a three-dimensional shape measuring device (manufactured by Keyence Corporation, product name: One Shot 3D Measuring Macroscope). Specifically, first, the three-dimensional shape of five analysis ranges (0.3 cm x 0.3 cm square areas) extracted from the surface (surface to be evaluated) to be the ground contact surface of the compact is measured using the above-mentioned measuring device. Then, the measurement results are filtered (2.5 mm) using software attached to the above-mentioned device to remove waviness components, the surface roughness Sa (μm) of each analysis range is calculated, and the average value of the five analysis ranges may be used as the surface roughness Sa of the powder compact. When extracting five analysis ranges, it is desirable that each analysis range is separated by 0.3 cm or more, but if the size of the powder compact is small, it is acceptable for some of the analysis ranges to overlap.

[0063] The impregnation step is a step of impregnating the linked body with a thermosetting composition. In this embodiment, thermosetting refers to the property of being hardened by heating more than before heating. In this embodiment, impregnation refers to penetrating a low-viscosity liquid material (in this embodiment, a thermosetting composition) having a viscosity of 200 mPa·s or less into the inside of the molded body in the linked body or between the molded bodies. Hereinafter, the hardening of the thermosetting composition by heating more than before heating may be simply referred to as thermosetting.

[0064] In the impregnation step, the linked body may be impregnated with the thermosetting composition by immersing the linked body in the thermosetting composition, or the linked body may be impregnated with the thermosetting composition by dripping the thermosetting composition onto the linked body and allowing it to soak in. When the linked body is impregnated with the thermosetting composition, for example, a vacuum may be applied to promote penetration. The impregnation step is performed while the linked body is maintained.

[0065] The viscosity of the thermosetting composition is 200 mPa·S or less, preferably 100 mPa·S or less, more preferably 50 mPa·S or less, even more preferably 15 mPa·S or less, and most preferably 10 mPa·S or less. If the viscosity of the thermosetting composition is 200 mPa·S or less, impregnation in the impregnation step is carried out properly, and the strength of the bonded magnet after the curing step described below tends to be increased.

[0066] The thermosetting composition is not particularly limited as long as it is thermosetting. The thermosetting composition may contain a thermosetting monomer, a thermosetting prepolymer, a thermosetting polymer, or the like. Examples of the thermosetting monomer include norbornene-based monomers, epoxy-based monomers, phenol-based monomers, acrylic-based monomers, and vinyl ester-based monomers. Examples of the norbornene-based monomers include tricyclo[5.2.1.0 2,6 ]Deca-3,8-diene (dicyclopentadiene), tricyclo[5.2.1.0 2,6 ]decane-3-ene, bicyclo[2.2.1]hepta-2,5-diene (2,5-norbornadiene), bicyclo[2.2.1]hept-2-ene (2-norbornene), bicyclo[3.2.1]oct-2-ene, 5-ethylidene-2-norbornene, bicyclo[2.2.1]hept-5-ene-2,3-dicarboxylic anhydride, 5-vinylbicyclo[2.2.1]hept-2-ene, tetracyclo[6.2.1.1 3,6 .0 2,7 ]dodec-4-ene, etc. Thermosetting prepolymers include epoxy resins, phenolic resins, melamine resins, guanamine resins, unsaturated polyesters, vinyl ester resins, diallyl phthalate resins, silicone resins, alkyd resins, furan resins, acrylic resins, urea resins, allyl carbonate resins, etc. Thermosetting polymers include polyurethane resins, polyimide resins, polyester resins, etc.

[0067] The thermosetting composition may contain a polymerization initiator and a curing agent. Examples of the initiator include Grubbs' catalyst (ruthenium carbene complex), dihalogen, and azo compounds. Examples of the curing agent include amine-based curing agents, acid anhydride-based curing agents, polyamide-based curing agents, imidazole-based curing agents, phenolic resin-based curing agents, polymercaptan resin-based curing agents, polysulfide resin-based curing agents, organic acid hydrazide-based curing agents, and isocyanate-based curing agents. Examples of the amine-based curing agents include diaminodiphenylsulfone, metaphenylenediamine, diaminodiphenylmethane, diethylenetriamine, and triethylenetetramine.

[0068] The curing step is a step of curing the thermosetting composition impregnated in the linked body to increase the strength (mechanical strength) of the linked body. In the curing step, the impregnated thermosetting composition is cured while the linked body is maintained. The linked body that has undergone the curing step is the bonded magnet according to this embodiment. The curing step is performed after the impregnation step. The thermosetting composition is cured in the curing step by a heat treatment for heating the linked body. The thermosetting composition impregnated in the linked body molded body is cured, and a crosslinked structure of the thermosetting resin that fixes the positional relationship between the particles of the magnetic powder is constructed between the particles. The particles and the thermosetting resin may be chemically bonded, or may be in a state of being bonded by inter-surface force. In addition, the thermosetting composition impregnated between the linked body molded bodies (between the grounding surfaces) is cured, and the linked body molded bodies are joined to each other.

[0069] The heat treatment temperature for heating the linked body is not particularly limited, but is preferably 100° C. or higher and 150° C. or lower, and more preferably 110° C. or higher and 130° C. or lower. If the temperature is lower than 100° C., the curing of the thermosetting composition does not proceed sufficiently, resulting in insufficient strength. If it is desired to further increase the strength, the secondary curing is performed at 150° C. or higher and 180° C. or lower, whereby greater strength can be achieved.

[0070] The heat treatment time is not particularly limited, but is preferably 1 minute or more and 120 minutes or less, and more preferably 3 minutes or more and 60 minutes or less. If it is less than 1 minute, the curing of the thermosetting composition does not proceed sufficiently, resulting in insufficient strength. If the secondary curing time is 1 minute or more and 120 minutes or less, and if it exceeds 120 minutes, the oxidation of the thermosetting composition by air proceeds, tending to result in insufficient strength.

[0071] In the curing step, a resin layer formed by curing the thermosetting composition may be formed between the ground surfaces of the molded bodies in the connected body, i.e., between one adjacent molded body and the other adjacent molded body. When forming this resin layer, the maximum thickness of the resin layer is preferably 2 μm or more and 50 μm or less. This resin layer can be formed integrally with the resin formed by curing the thermosetting composition impregnated in the molded body by allowing the thermosetting composition impregnated in the connected body to penetrate into the gap between the ground surfaces caused by the unevenness of the ground surfaces and filling the gap. In other words, the maximum thickness of the resin layer is the distance between the adjacent molded bodies in the bonded magnet, which is the connected body that has undergone the curing step (the maximum distance between the ground surface of one molded body and the ground surface of the other molded body).

[0072] The bonded magnet, which is a connected body that has undergone the hardening process, has as its minimum unit the structure of bonded magnet 100 shown in Figure 1. The bonded magnet obtained through the hardening process may be magnetized, for example, to strengthen its magnetic force.

[0073] In this way, according to the manufacturing method of the bonded magnet of this embodiment, it is possible to manufacture a bonded magnet by joining two or more molded bodies. Therefore, with the manufacturing method of the bonded magnet of this embodiment, it is possible to easily mold a bonded magnet of any shape by arranging and joining multiple molded bodies in any shape. This makes it possible to easily realize a bonded magnet of a complex shape, for example, when a magnet of that shape is required for precise magnetic control. EXAMPLES

[0074] The bonded magnet and the manufacturing method of the bonded magnet according to this embodiment will be described below based on examples.

[0075] <Example 1> The bonded magnet according to Example 1 was manufactured and evaluated as follows.

[0076] (Preparation of magnetic powder) In the mortar, as a magnetic filler, 2 Fe 14 B (True specific gravity: 7.6g / cm 3 A magnetic powder (product name: MF15P, manufactured by Aichi Steel Corporation) was prepared, which is a powder of a magnetic material of the above formula. The particle size of this magnetic powder is a median diameter of 120 μm. The aspect ratio of this magnetic powder is 1.3. The magnification rate during SEM observation when measuring the aspect ratio was 100 times. In addition, 2-(bicyclo[2.2.1]hept-5-en-2-yl)ethyltrimethoxysilane (model: X-88-351, manufactured by Shin-Etsu Chemical Co., Ltd.) was prepared as a silane coupling agent. In addition, fatty acid ester type sorbitan trioleate (manufactured by Kao Corporation, model: Rheodol SP-O30V) was prepared as a non-ionic surfactant.

[0077] Then, 300g of this magnetic powder was placed in a stirring container (mortar), 3g of the silane coupling agent was added to the magnetic powder in this container, and the mixture was stirred with a pestle for 5 minutes. After this stirring, the container was left open for 30 minutes and dried at room temperature. Then, 3g of the nonionic surfactant was added, and the mixture was stirred with a pestle for 5 minutes. After this stirring, the container was left open for 30 minutes to obtain a magnetic powder after surface treatment.

[0078] (molding process) Next, the surface-treated magnetic powder was compression molded as follows to obtain a molded body as a precursor of the bonded magnet.

[0079] A mold with an annular cavity inside was used for compression molding. The cavity of this mold had an outer diameter of 16 mm, an inner diameter of 10 mm, and a height of 3 mm. 6.5 g of the surface-treated magnetic powder was then placed in the mold, and with the upper and lower punches attached, it was compressed at 3 t / cm. 2The upper and lower punches were compressed with a molding pressure of 1000 to obtain a ring-shaped compact (having a through hole in the center of the disk).

[0080] The production of the green bodies was carried out twice for the production of one bonded magnet. That is, a set of two green bodies was obtained for the production of one bonded magnet. The specific gravity of these green bodies was 5.56 g / cm, the average value of the four green bodies. 3 The specific gravity of the compact was calculated by measuring the mass, area and thickness of the compact and dividing the mass by the volume (= area x thickness). The theoretical filling rate of the compact derived from this specific gravity was 73%. The theoretical filling rate is the value obtained by dividing the specific gravity of the compact by the true specific gravity of the magnetic material in the magnetic powder, and then multiplying the result by 100.

[0081] (Connection process) Next, a connected body was formed as follows. First, a cylindrical metal rod with a diameter of 10 mm and a length of 30 mm was prepared, and this metal rod was inserted into the holes of the rings of the two molded bodies (two were randomly selected from the four). Then, the upper surface of the ring of one molded body was abutted against the lower surface of the ring of the other molded body to ground the molded bodies. Furthermore, a mold-like container was prepared that had a shape that could wrap the two molded bodies held by the metal rod without any gaps, and these molded bodies were contained in the container together with the metal rod. Then, the molded bodies were restrained by this container in a grounded state, and the positions of the connected bodies were fixed to each other to form a connected body. The connected body has a shape in which two molded bodies formed in an annular shape are stacked in the axial direction of the ring (hereinafter, this may be referred to as a stacked shape). Hereinafter, the method of forming a connected body by directly grounding the surfaces of the molded bodies in this way and maintaining the state in which the connected body is maintained will be referred to as a direct connection.

[0082] The surface roughness of the grounding surface of each of the four molded bodies was 5.7 μm, which was the average value of the four grounding surfaces. No surface treatment such as polishing was performed on each grounding surface when the grounding and connecting bodies were formed. Furthermore, no adhesive was applied to the grounding surface when the grounding and connecting bodies of the molded bodies were formed.

[0083] (Impregnation process) Next, the linked bodies were impregnated with the thermosetting composition as follows. The lid of the mold-shaped container was opened, and while the linked bodies were maintained, 0.5 g of liquid thermosetting composition was dropped and held for 30 seconds to impregnate the linked bodies. As the liquid thermosetting composition, a mixture of 100 parts by weight of dicyclopentadiene monomer (viscosity: 3 mPa·s, density: 1.02 g / cc) and 0.3 parts by weight of dichloro[1,3-bis(2,6-isopropylphenyl)-2-imidazolidinylidene](2-isopropylphenylmethylene)ruthenium(III) as a reaction initiator was used.

[0084] (hardening process) The connected body impregnated with the thermosetting composition was heated at 120°C for 15 minutes while contained in a mold-shaped container to cure the thermosetting composition, thereby obtaining a bonded magnet according to this example. The specific gravity of this bonded magnet was 5.86 g / cm 3 The specific gravity of the bonded magnet was calculated by measuring the mass, area and thickness of the bonded magnet and dividing the mass by the volume (= area x thickness).

[0085] (Cross-section observation) The bonded magnet according to this embodiment was further observed in cross section to observe the grounding portion between the molded bodies. In this cross section observation, a cross section including the grounding portion between the molded bodies and perpendicular to the grounding portion was formed on the bonded magnet. The vicinity of the grounding portion was then observed with a scanning electron microscope (SEM, Hitachi High-Technologies Corporation, model: SU-3500) at a magnification of 200 times, over a range of 1000 μm along the grounding surface. From this observation, it was found that a resin layer of up to 4 μm was formed between the grounding surfaces forming the bonded magnet. This resin layer is considered to be a resin layer formed by hardening the thermosetting composition impregnated into the connecting body.

[0086] (strength) The strength of the bonded magnet obtained in the above manner (however, different from the one for which the cross-sectional observation was performed) was evaluated. In this example, the radial crushing strength was measured as the strength of the bonded magnet. The radial crushing strength was measured using a precision universal testing machine (manufactured by Shimadzu Corporation, model: Autograph AG-IS 20kN). Specifically, the above testing machine was used to apply pressure from one side of the ring of the bonded magnet toward the other side (i.e., downward) at a pressing speed of 500 mm / min, and the pressure at which the bonded magnet cracked was determined, and this was taken as the radial crushing strength (MPa). Hereinafter, this test may be referred to as the radial crushing strength test. The radial crushing strength of the bonded magnet in this example was 30.5 MPa.

[0087] Table 1 lists the information on the manufacturing conditions and evaluation results for the manufacturing process of the bonded magnet according to this embodiment. Table 1 shows the information on the manufacturing conditions and evaluation results for the bonded magnet according to this embodiment, including the manufacturing conditions and evaluation results, the shape of the molded body, the molding pressure of the molded body, the specific gravity of the molded body, the theoretical packing rate of the molded body, whether the ground surface was polished, the surface roughness of the ground surface when the connected body was formed, whether the molded body before the connected body was impregnated with the thermosetting composition, the position of the ground surface when the connected body was formed, the connecting method when the connected body was formed, whether the connected body was impregnated with the thermosetting composition, the specific gravity of the manufactured bonded magnet, the thickness of the resin layer of the bonded magnet observed by cross-sectional observation, the strength of the bonded magnet, and the specific gravity of the bonded magnet.

[0088] [Table 1]

[0089] <Example 2> Unlike Example 1, the molding pressure in Example 1 was set to 1t / cm 2 Other than that, a bonded magnet was obtained in the same manner as in Example 1. As in the case of Example 1, Table 1 lists information related to the manufacturing conditions and evaluation results of the bonded magnet according to this example.

[0090] <Example 3> Unlike Example 1, the molding pressure in Example 1 was set to 10 t / cm 2Other than that, a bonded magnet was obtained in the same manner as in Example 1. As in the case of Example 1, Table 1 lists information related to the manufacturing conditions and evaluation results of the bonded magnet according to this example.

[0091] <Example 4> Unlike Example 1, the ground surface was polished with sandpaper (#800) before forming the connected body, but the bonded magnet was obtained in the same manner as in Example 1. As in Example 1, Table 1 lists information related to the manufacturing conditions and evaluation results of the bonded magnet of this example.

[0092] <Example 5> Unlike Example 1, the ground surface was polished with sandpaper (#320) before forming the connected body, but the bonded magnet was obtained in the same manner as in Example 1. As in Example 1, Table 1 lists information related to the manufacturing conditions and evaluation results of the bonded magnet according to this example.

[0093] <Example 6> In this example, the surface-treated magnetic powder produced in the same manner as in Example 1 was used in the molding process to obtain a flat plate-shaped compact using a mold different from that used in Example 1, and a connected body was formed by grounding the compacts together in a state different from that of Example 1. A bonded magnet was obtained in the same manner as in Example 1, except that the bonded magnet was produced from this connected body.

[0094] (molding process) In this example, a cylindrical die with a bottom and a circular cavity when viewed from above was used. The cavity had an inner diameter of 30 mm and a depth of 1 mm. 3.5 g of the surface-treated magnetic powder obtained in the same manner as in Example 1 was filled into this die, and a punch with a diameter of 3 cm was attached to press the powder at 3 t / cm. 2 The punch was compressed at a molding pressure of 1000 MPa to obtain a disk-shaped green compact having a diameter of 30 mm and a thickness of 0.8 mm.

[0095] Then, a square piece of the molded body having a side length of 10 mm was cut out from the circular center of the disk-shaped molded body with a cutter knife.

[0096] (Connection process) Next, a mold-like container having a rectangular cavity of 2 cm x 1 cm was prepared, and the two molded body pieces were placed in the cavity with their sides (edges) in contact with each other and grounded, and then restrained to form a connected body. That is, in this embodiment, the side of the molded body piece (the cut surface when cut with a cutter knife) serves as the ground surface. The connected body is a rectangle (hereinafter, may be referred to as a rectangular plate) in which square plate-like molded bodies are arranged adjacent to each other.

[0097] (Impregnation process) The liquid thermosetting composition was dripped onto this connected body in the same manner as in Example 1 to impregnate the connected body.

[0098] (hardening process) Thereafter, the thermosetting composition was cured in the same manner as in Example 1 to obtain a bonded magnet according to this example. This bonded magnet has a rectangular plate shape when viewed from above.

[0099] (Cross-section observation) The bonded magnet according to this example was further observed for the thickness of the resin layer in the same manner as in Example 1.

[0100] (strength) The strength of the bonded magnet according to this embodiment was evaluated for fracture by applying a predetermined bending stress (hereinafter referred to as a bending test), unlike that of Example 1. First, a metal base measuring 6 cm x 6 cm x 2 cm was prepared. Then, the entire plate portion of the rectangular bonded magnet from the center to one end in the longitudinal direction was placed on the base, and the entire plate portion from the center to the other end was positioned so as to protrude from the base. Furthermore, an aluminum plate measuring 6 mm x 6 mm x 2 mm was placed on the bonded magnet so as to overlap with the base when viewed from above. That is, the aluminum plate was placed only on the plate portion from the center to one end in the longitudinal direction of the rectangular bonded magnet, covering the entire plate portion. Then, a weight of 300 mg was placed on the end of the bonded magnet that protruded from the base (the plate portion on the other end side) that was away from the base, and a bending stress was applied to the bonded magnet to evaluate whether fracture would occur. In this evaluation, the bonded magnet according to this embodiment was not fractured (did not break).

[0101] As in the case of Example 1, Table 1 lists information related to the manufacturing conditions and evaluation results of the bonded magnet according to this example.

[0102] <Comparative Example 1> Unlike Example 1, when forming the connected bodies, the connected bodies were bonded with an adhesive, and a bonded magnet was obtained in the same manner as in Example 1, except that the impregnation step was omitted.

[0103] When forming a connected body, 10 mg of adhesive was applied to one of the grounding surfaces of the molded bodies, and the molded bodies were grounded to each other via the adhesive. When grounding the molded bodies to each other, a metal rod was inserted into the holes in the rings of these two molded bodies. In this comparative example, an α-cyanoacrylate adhesive (Aron Alpha) was used as the adhesive. Hereinafter, forming a connected body by bonding the surfaces of the molded bodies to each other with an adhesive in this way is referred to as adhesive connection.

[0104] As in Example 1, information related to the manufacturing conditions and evaluation results of the bonded magnet according to this comparative example is listed in Table 1. In the bonded magnet according to this comparative example, the compact portion was destroyed (cracked) in the radial crushing strength test.

[0105] <Comparative Example 2> The procedure was the same as in Example 1, except that, unlike Example 1, the impregnation process was carried out separately for each compact before forming a connected body, and the impregnated compacts were bonded with an adhesive to obtain a bonded magnet.

[0106] When the molded bodies were impregnated with the thermosetting composition, a mold-shaped container that could enclose the molded bodies without gaps was prepared, and the molded bodies were placed in the container. Then, the lid of the mold-shaped container was opened, and 0.25 g of the same thermosetting composition as that used in the impregnation step of Example 1 was dropped onto each molded body to impregnate it.

[0107] When forming a connected body, 10 mg of adhesive was applied to one of the grounding surfaces of the impregnated molded body, and the impregnated molded bodies were grounded to each other via the adhesive. In this comparative example, the same adhesive as used in Comparative Example 1 was used. Thereafter, the thermosetting composition was cured in the same manner as in Example 1 to obtain the bonded magnet of this example. As in the case of Example 1, Table 1 lists information related to the manufacturing conditions and evaluation results of the bonded magnet of this comparative example. In the bonded magnet of this comparative example, the adhesive layer (adhesive layer) was destroyed (cracked) in the radial crushing strength test.

[0108] <Comparative Example 3> Unlike Example 6, when forming the connecting body, the connecting body was joined with an adhesive, the impregnation process was omitted, and the heating time in the curing process was set to 30 minutes. Except for this, a bonded magnet was obtained in the same manner as in Example 6.

[0109] When forming the connected body, 10 mg of adhesive was applied to one of the grounding surfaces of the compacts, and the compacts were grounded to each other via the adhesive and then contained and restrained in a cavity as in Example 6. In this comparative example, the same adhesive as used in Comparative Example 1 was used. Thereafter, the connected body was heated at 120°C for 30 minutes while contained in a mold-shaped container as in Example 6, but with the heating time changed, to obtain a bonded magnet according to this comparative example.

[0110] As in Example 1, information related to the manufacturing conditions and evaluation results of the bonded magnet according to this comparative example is listed in Table 1. In the bonded magnet according to this comparative example, the center part of the molded body was destroyed (broken) in the bending test.

[0111] As shown in Table 1, the bonded magnets according to the examples have higher mechanical strength than the bonded magnets according to the comparative examples formed in the same shape (laminated or rectangular plate). Specifically, the bonded magnets of the examples 1-5 formed in a laminated shape have significantly higher radial crushing strength than the bonded magnets of the comparative examples 1 and 2 formed in a similar laminated shape. In addition, the bonded magnet of the example 6 formed in a rectangular plate shape is stronger against bending than the bonded magnet of the comparative example 3 formed in a rectangular plate shape, and there was no breakage of the molded body part or breakage with the ground surface as the fracture surface. It is considered that the bonded magnets of the comparative examples 1 and 3 did not have a sufficient strength of the molded body because the connected body (molded body) was not impregnated with the thermosetting composition. It is considered that the strength of the adhesive layer of the bonded magnet of the comparative example 2 was insufficient, or the interface between the adhesive layer and the set surface was weak. It is considered that the strength of the bonded magnet is increased by impregnating the connected body with the thermosetting resin as a whole, as in the bonded magnets of the examples 1-6.

[0112] The results of Examples 1-6 show that the bonded magnet according to this embodiment can achieve high strength regardless of the shape of the compact, which is the smallest unit for constructing a bonded magnet. It also shows that by changing the shape of the compacts that are connected, it is possible to construct (manufacture) a bonded magnet of any shape.

[0113] In addition, the bonded magnets of Examples 1 to 6 all have a specific gravity of 5 g / cm 3From the above, it is seen that the filling rate of the magnetic powder is sufficiently high.

[0114] In comparison between Examples 1-5 and Comparative Examples 1 and 2, it can be seen that by setting the surface roughness of the ground contact surface to 50 μm or less, preferably 30 μm or less, the strength is significantly increased compared to Comparative Examples 1 and 2 in which the impregnation process was omitted. In particular, the results of Examples 1-5 show that the strength is increased when the thickness of the resin layer is less than 80 μm, preferably less than 50 μm. The results of Examples 1-5 show that there is a roughly positive correlation between the surface roughness of the ground contact surface and the thickness of the resin layer. For example, as in Examples 4 and 5, it can be seen that the thickness of the resin layer can be controlled by controlling the surface roughness of the ground contact surface by polishing the ground contact surface.

[0115] In this manner, it is possible to provide a bonded magnet manufacturing method and a bonded magnet that can realize a bonded magnet with a high magnetic powder filling rate and in any shape.

[0116] Note that the embodiments disclosed in this specification are merely examples, and the embodiments of the present disclosure are not limited thereto, and may be modified as appropriate within the scope of the purpose of the present disclosure. [Industrial Applicability]

[0117] The present disclosure is applicable to bonded magnets and methods of manufacturing bonded magnets. [Explanation of symbols]

[0118] 1: First molded body 10: Particles 100: Bonded magnet 2:Second molded body 3:Thermosetting resin 4: Resin layer

Claims

1. a molding step of compressing and molding the magnetic powder to obtain a green body; a grounding step in which two or more of the molded bodies are grounded and held together to form a connected body; and an impregnation step of impregnating the connector with a thermosetting composition, A method for producing a bonded magnet, wherein the thermosetting composition has a viscosity of 200 mPa·s or less.

2. The method for producing a bonded magnet according to claim 1 , wherein the surface roughness of the contact surface of each of the molded bodies in the connected body is set to 50 μm or less.

3. The method further includes a curing step of curing the thermosetting composition impregnated in the connector, In the curing step, forming a resin layer between one of the molded bodies and the other of the molded bodies by hardening the thermosetting composition; The method for producing a bonded magnet according to claim 1 or 2, wherein the thickness of the resin layer is set to be 2 μm or more and 50 μm or less.

4. In the molding step, the mixed powder of the magnetic powder and the surface treatment agent is compression molded to form the molded body, 3. The method for producing a bonded magnet according to claim 1, wherein the surface treatment agent is mixed in an amount of 5 parts by mass or less with respect to 100 parts by mass of the magnetic powder.

5. a first molded body and a second molded body in which a magnetic powder is fixed with a thermosetting resin; A resin layer disposed between the first molded body and the second molded body, the resin layer is formed of the thermosetting resin, A bonded magnet, wherein the resin layer has a maximum thickness of 2 μm or more and 50 μm or less.

Citation Information

Patent Citations

  • Method for manufacturing bonded magnet and bonded magnet

    JP2020109840A